Welcome message from the technical program chair - Ammar, Reda; El-Dessouki, Ayman (The 10th IEEE International Symposium on Signal Processing and Information Technology, 2010)
I would like to welcome you to the 10 th IEEE International Symposium on Signal Processing and Information Technology in Luxor, Egypt. This is the 10 th in a series of Symposia bridging the areas of Signal Processing and Information Technology and bringing the research communities together. ISSPIT offers a forum for international experts in these overlapping fields to discuss their results and explore research opportunities.